DOS PASAJES CONFLICTIVOS EN LA EDICIÓN COMENTADA DEL ASINVS AVREVS DE BEROALDO (II, 26 Y IV, 26) Y SU REPERCUSIÓN EN LA TRADUCCIÓN DE LÓPEZ DE CORTEGANA - Pérez Custodio, María Violeta (Myrtia, 1996)
This work tries to show that the translations of the classical texts done during the Renaissance can not be valued in relation to the respective modern editions. On the contrary, it is methodologically essential to compare the translation with the renacentist Latin edition. Otherwise we can consider faults in the renacentist translation what are just literal translations of passages in the contemporary Latin edition. In order to do this two passages from the translation of Apuleius’ ’Asinus aureus’ published by López de Cortegana about 1525 are analysed.